Social Representations and Focus Group: a study on the assessment of learning in distance education. - Vania Maria de Oliveira Vieira; Marilene Ribeiro Resende (Universidade Estadual Paulista Júlio de Mesquita Filho, 2013)
This article derives partially from a theoretical-methodological research, carried out with the support of Social Representations Theory. It focuses specifically on discussions and reflections on learning assessment in distance education. The data were collected from focus groups, gathered from graduating students of Pedagogy of two poles of an Educational Institution, Cariacica and Colatina poles, in the State of Espírito Santo. The objective was to identify the social representations which the graduating students of Pedagogy in distance education built about the assessment of learning. The data analysis identified three key words: contradictions, rituals and perceptions which were translated into three unities of meaning. These unities are associated with the social representations, built by those students. From their experiences, speeches, pictures and viewpoints, they organized and transformed their representations into feelings which denote that assessment is primordial and necessary for learning in the course; yet at the same time, they met contradictions, between what is taught in theory, and what is experienced in practice, what leads them to fight for a more humane evaluation process.